Determinant That Effect on Fraud Detection Capabilities by Auditors - Anita Wahyu Indrasti S. E, M. Akt; Conni Novita Sari (International Journal of Business Studies, 2019)
This study aims to determine the effect of professional skepticism, auditor experience, whistleblowing and red flags on the ability to detect fraud by the auditor. The population in this study is the auditor who works at the Public Accounting Office (KAP) in the South Jakarta area. The sampling technique uses convenience sampling. This research data was obtained from a questionnaire that had been previously shared with the auditors working at the Public Accounting Firm in the South Jakarta area. The type of data used is primary data. The method of data collection is a survey, using a questionnaire. The analysis tool uses multiple linear regression. The results showed that the experience of auditors, whistleblowing and red flags did not significantly influence the ability of fraud detection by auditors, whereas professional skepticism had a significant effect on the ability to detect fraud by auditors. The value of the determination coefficient obtained is 0.236, which means that the independent variables used in this research model are able to explain 23.6% variation in the dependent variable and the remaining 76.4% is explained by other variables outside of this study.